2019
DOI: 10.1021/acs.est.8b05814
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Response of Water-Soluble Fractions in Atmospheric Fine Particulates: A Seasonal Observation in 10 Large Chinese Cities

Abstract: Spatiotemporal trends in pro-inflammatory (interleukin (IL)-6 and IL-8) release after exposure to the water-soluble fractions (WSFs) of PM2.5 sampled in 10 large Chinese cities over 1 year were investigated. Chemical components (water-soluble ions, metal(loid) elements, water-soluble organic carbon (WSOC), humic-like substances (HULIS), and endotoxins) in PM2.5 samples were measured, and the molecular structure of WSOC was also analyzed by nuclear magnetic resonance. Changes in DNA methylation and gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 40 publications
(114 reference statements)
4
30
0
Order By: Relevance
“…In addition, DNAm of five non-imprinted genes was also determined and analyzed. Two predicted imprinted genes (CYP1B1 and APBA1) were classified as non-imprinted genes during statistical analysis and three non-imprinted genes (RASSF2, MGMT, and APC) were potential PM2.5 biomarkers in accordance with previous studies (Breton and Marutani, 2014;Ding et al, 2016;Ma et al, 2019). Therefore, it is necessary to further study whether the above 18 germline ICRs are more sensitive to PM2.5 exposure when they are compared to non-imprinted genes.…”
Section: Dna Methylationsupporting
confidence: 57%
See 1 more Smart Citation
“…In addition, DNAm of five non-imprinted genes was also determined and analyzed. Two predicted imprinted genes (CYP1B1 and APBA1) were classified as non-imprinted genes during statistical analysis and three non-imprinted genes (RASSF2, MGMT, and APC) were potential PM2.5 biomarkers in accordance with previous studies (Breton and Marutani, 2014;Ding et al, 2016;Ma et al, 2019). Therefore, it is necessary to further study whether the above 18 germline ICRs are more sensitive to PM2.5 exposure when they are compared to non-imprinted genes.…”
Section: Dna Methylationsupporting
confidence: 57%
“…However, sensitive and specific human biomarkers of PM2.5 exposure is still needed. DNAm may be involved in regulating the process of oxidative damage and inflammation, which leads to disease (Chen et al, 2015;Dai et al, 2017;de et al, 2018;Lodovici and Bigagli, 2011;Ma et al, 2019;Shi et al, 2019). The reversibility of DNAm makes it more important to find specific biomarkers of DNAm and contributes to feasibility of disease prevention and treatment (Yoo and Jones, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In our results, water-soluble ions in the Bayan Obo mining area account for 26.48 and 37.18 % of PM 10 and PM 2.5 , respectively, which is similar to the results of other studies. Ma et al have shown that water soluble fraction constituted more than 39 % of the PM2.5 which were collected from 10 urban cities in China [ 14 ]. The water-soluble inorganic ions in PM10 have also a greater proportion.…”
Section: Discussionmentioning
confidence: 99%
“…A former study has demonstrated a strong relationship between IL-6/TNF-α secretion with the presence of Cu and Zn from anthropogenic sources PM2.5 in Mexicali (Osornio-Vargas et al 2011). According to a recent investigation in which PM2.5 was sampled in 10 large Chinese cities over 1 year, IL-6 was signi cantly correlated with Pb, and endotoxin (Ma et al 2019). Additional, it has reported that Mn and Cr were associated with IL-8 production in epithelial cells.…”
Section: Discussionmentioning
confidence: 99%